Analysis of Determinants of Satisfaction Using E-Learning in Elementary School Students - Faroqi, Asif; Wulansari, Anita; Suryanto, Tri Lathif Mardi; Pratama, Arista; Mukaromah, Siti (ISB Atma Luhur, 2023)
The COVID-19 pandemic, a global health crisis, has made many sectors carry out their activities in new ways, including the education sector. Teaching and learning activities should not be conducted face-to-face during the COVID-19 pandemic. As a result, all learning activities are diverted through e-learning. Therefore, an evaluation of the use of e-learning needs to be carried out to ensure its practical use and a positive impact. This study evaluates the factors that affect the satisfaction of e-learning users. Data were collected by surveying 205 elementary school students in the 4th, 5th, and 6th grades, then analyzed using the structural equation model technique. The results showed that Technical System Quality, Information Quality, Learner Quality, and Perceived Usefulness affected the satisfaction of e-learning users. These results can be suggestions for schools to fix and improve e-learning performance so that students and teachers no longer have difficulties when an event requires online teaching and learning activities.